Evaluación cefalométrica del perfil de tejidos blandos en adultos jóvenes de Medellín - Arismendi-Montoya, Alvaro José; Castaño-Ibarra, Gabriel Alberto; Jaramillo-Vallejo, Pedro María (Revista Facultad de Odontología Universidad de Antioquia, 2017)
The orthodontic treatment goal is the achievement of optimal facial harmony with the best possible occlusal function within therapeutic limits. When a maxillofacial deformity surpasses these limits, the intervention of the surgical - orthodontic interdisciplinary team is necessary. This team uses Legan and Burstone's soft tissue analysis for diagnostic purposes, which is based on North american population standards and doesn't account for the ehtnic variation on different populations around the globe. The purpose of this study is to determine the differences between a population sample of Medellin (Colombia) and samples from North America (4) and Bogota (Colombia)(") when using the aforementioned analysis. 102 young adults (51 men and 51 women with ages between 18 and 29 years) from Medellin, with parents and grand parents from Antioquia r were studied by applying Logan and Burstone's analysis. The obtained data was compared with the other two samples demonstrating results that were significantly different and highly recommending the use of the values obtained in this study on the local population.